Translation and it’s Types - Abdullayeva Zarina Shukhrat kizi (Scientific Trends, 2024)
When we talk about translation, we’re not just referring to word-for-word substitutions. It encompasses the art of conveying ideas, making them accessible and engaging to new audiences in different languages. As globalization expands our horizons, the need for various types of translations has surged, becoming essential in industries such as healthcare, finance, and law. In this article we mention the translation and it's types.
Keywords: Translation, globalization, legal translation, technical translation, literary translation, script translation, administrative translation.